2012
DOI: 10.1016/j.ijrobp.2012.07.2038
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Treatment Management: Incorporating a Predictive Tumor Response Model Into Robust Prospective Treatment Planning for Non-small Cell Lung Cancer

et al.

Abstract: Purpose-We hypothesized that a treatment planning technique that incorporates predicted lung tumor regression into optimization, predictive treatment planning (PTP), could allow dose escalation to the residual tumor while maintaining coverage of the initial target without increasing dose to surrounding organs at risk (OARs).Methods and Materials-We created a model to estimate the geometric presence of residual tumors after radiation therapy using planning computed tomography (CT) and weekly cone beam CT scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Small degrees of uncertainty (≤ 3 mm in any direction) appear to lead to LF and should be accounted for with robust planning. Recently, several groups have proposed using robust probabilistic planning to replace the concept of PTV in photon therapy . The plan robustness quantification tools developed for this study could help design knowledge‐based anisotropic margins in our clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Small degrees of uncertainty (≤ 3 mm in any direction) appear to lead to LF and should be accounted for with robust planning. Recently, several groups have proposed using robust probabilistic planning to replace the concept of PTV in photon therapy . The plan robustness quantification tools developed for this study could help design knowledge‐based anisotropic margins in our clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the findings were evaluated in a qualitative manner. 19 relevant publications were identified (Figure1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Search Strategy Methodologymentioning
confidence: 99%
“…Nine studies [24][25][26][27][28][29][30][31][32] were identified that outlined novel concepts which may prove to be a future basis for personalised RT prescriptions, findings are summarised in Table 3. These studies can be broadly categorised depending on the patient specific feature they are utilising as a basis for personalisation.…”
Section: Future Directions Of Personalised Radiotherapy Prescriptionsmentioning
confidence: 99%
See 2 more Smart Citations